Integral foam molding of light metals technology, foam physics and foam simulation - Koerner, Carolin (Engineering materials, 2008)
The development of cost-effective techniques to produce metal parts with integrated cellular structure is the newly developed process of integral foam molding. This book shows in three parts the technology, the fundamentals and the simulation models for the Integral Foam Molding of Light Metals Part I: “Technology” shows for the first time that foaming of metals is possible by applying molding techniques very similar to polymer integral foam molding. It introduces and discusses in detail a low pressure and a high pressure process of foam molding. Part II: “Physics” is devoted to the physics of foaming with special emphasis on the very short time scale which is characteristic for integral foam molding. Although very complex in detail, foam formation is shown to underlie simple evolution laws determined by the way how foam stabilization is realized. Part III: “Numerical Simulation” presents a new lattice Boltzmann approach for the treatment of free surfaces is developed and applied on foam evolution problems. For the first time, the numerical simulation of foam evolution starting from nucleation until decay is accessible. The interplay between hydrodynamics, capillary forces, gravity and bubble coalescence processes leads to complex phenomena such as topological rearrangements, avalanches, drainage, etc. without further model assumptions. Technology - Integral foam molding of metals - Structure and properties - Physics - Physics of foaming - Evolution laws - Endogenous stabilization - Numerical simulation - Theoretical approach - Lattice boltzmann model for free surface flow - Lattice boltzmann model for foam evolution.